2017
DOI: 10.1021/acsomega.7b00673
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Core/Shell ZnO/rGO Nanoparticles by Calcination of ZIF-8/rGO Composites and Their Photocatalytic Activity

Abstract: A facile two-step method was developed to prepare core/shell ZnO/rGO particles from ZIF-8/rGO composites. ZIF-8 particles were first grown at the surface of rGO sheets. Next, ZIF-8 particles were transformed into ZnO particles by thermal decomposition under air at 500 °C. All materials were characterized by scanning electron microscopy, transmission electron microscopy, X-ray diffraction, Raman spectroscopy, thermogravimetric analysis, and Brunauer–Emmett–Teller analyses. Results obtained show that ZIF-8 parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 79 publications
(32 citation statements)
references
References 51 publications
3
27
0
Order By: Relevance
“…3.2 eV and a large exciton binding energy (60 meV at room temperature). ZnO exhibits good photosensitivity, high carrier mobility and is therefore used in numerous photocatalytic applications but also in photodetectors and in solar cells ,. However, the use of ZnO as photocatalyst for practical applications is generally restricted because (1) it can only be activated by UV‐light due to its wide bandgap, (2) photogenerated electron/hole pairs exhibit a short lifetime and (3) its photocorrosion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3.2 eV and a large exciton binding energy (60 meV at room temperature). ZnO exhibits good photosensitivity, high carrier mobility and is therefore used in numerous photocatalytic applications but also in photodetectors and in solar cells ,. However, the use of ZnO as photocatalyst for practical applications is generally restricted because (1) it can only be activated by UV‐light due to its wide bandgap, (2) photogenerated electron/hole pairs exhibit a short lifetime and (3) its photocorrosion.…”
Section: Introductionmentioning
confidence: 99%
“…Doping of ZnO with metal,, or non‐metal elements, coupling with metal nanoparticles or with graphene derivatives,, or constructing heterostructures with low bandgap semiconductors, have been demonstrated to be effective strategies to enhance both the charge separation and the visible light photoresponse of ZnO‐based photocatalysts.…”
Section: Introductionmentioning
confidence: 99%
“…In XRD spectra of RGO/B−TiO 2 , the disappearance of GO diffraction peaks indicated that GO was reduced to RGO under the hydrothermal condition. As previously reported, a peak at 2θ=25.1° was attributed to the layer spacing of RGO . Therefore, the RGO layer reflection combined with the characteristic peak of TiO 2 at 25.3° (Figure d).…”
Section: Resultsmentioning
confidence: 95%
“…As previously reported, a peak at 2θ = 25.1°was attributed to the layer spacing of RGO. [42] Therefore, the RGO layer reflection combined with the characteristic peak of TiO 2 at 25.3° (Figure 2d). Compared with RGO/BÀ TiO 2 , the peaks of ZIF-8 at 2θ = 7.4°and 12.7°could be observed in Figure 2e, which proved the successful preparation of the ternary RGO/BÀ TiO 2 /2D-ZIF-8 composite.…”
Section: Introductionmentioning
confidence: 95%
“…[30][31][32] So, coupling RGO with magnetic metals could achieve a optimized impedance match and such dielectric/magnetic composites have been widely studied to obtain better absorbents. [33][34] Wei et al synthesized nanocomposite of Fe 3 O 4 @SnO 2 /RGO, the RLmin value is À 45.5 dB. [35] Liu et al reported Co 0.33 Ni 0.67 alloy and RGO composites as absorber, the absorption bandwidth (RL < À 10 dB) reaches up to 14.0 GHz.…”
Section: Introductionmentioning
confidence: 99%